A Pb isotopic resolution to the Martian meteorite age paradox - Bellucci, J.; Nemchin, A.; Whitehouse, M.; Snape, J.; Kielman, R.; Bland, Phil; Benedix, G. (ELSEVIER SCIENCE BV, 2016)
© 2015 Elsevier B.V. Determining the chronology and quantifying various geochemical reservoirs on planetary bodies is fundamental to understanding planetary accretion, differentiation, and global mass transfer. The Pb isotope compositions of individual minerals in the Martian meteorite Chassigny have been measured by Secondary Ion Mass Spectrometry (SIMS). These measurements indicate that Chassigny has mixed with a Martian reservoir that evolved with a long-term 238U/204Pb (µ) value ~ two times higher than those inferred from studies of all other Martian meteorites except 4.428 Ga clasts in NWA7533. Any significant mixing between this and an unradiogenic reservoir produces ambiguous trends in Pb isotope variation diagrams. The trend defined by our new Chassigny data can be used to calculate a crystallization age for Chassigny of 4.526±0.027 Ga (2s) that is clearly in error as it conflicts with all other isotope systems, which yield a widely accepted age of 1.39 Ga. Similar, trends have also been observed in the Shergottites and have been used to calculate a >4 Ga age or, alternatively, attributed to terrestrial contamination. Our new Chassigny data, however, argue that the radiogenic component is Martian, mixing occurred on the surface of Mars, and is therefore likely present in virtually every Martian meteorite. The presence of this radiogenic reservoir on Mars resolves the paradox between Pb isotope data and all other radiogenic isotope systems in Martian meteorites. Importantly, Chassigny and the Shergottites are likely derived from the northern hemisphere of Mars, while NWA 7533 originated from the Southern hemisphere, implying that the U-rich reservoir, which most likely represents some form of crust, must be widespread. The significant age difference between SNC meteorites and NWA 7533 is also consistent with an absence of tectonic recycling throughout Martian history.